1984
DOI: 10.1063/1.95247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argon ion implantation dose on silicon Schottky barrier characteristics

Abstract: Use of ultrasound for metal cluster engineering in ion implanted silicon oxide Appl. Phys. Lett. 90, 013118 (2007); 10.1063/1.2430055 Effect of aging on wettability of silicon surfaces modified by Ar implantation J. Appl. Phys. 92, 5872 (2002); 10.1063/1.1516866 Effect of antimony ion implantation on Alsilicon Schottky diode characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Any mechanism that modifies the properties of the interface such as the introduction of an interfacial layer [1][2][3][4], annealing [5,6], irradiation with gamma rays [7,8], protons [9][10][11][12][13][14] and neutrons [14][15][16], ion implantation, [17][18][19] and high-energy ion beam irradiation [20][21][22][23][24][25][26] are found to alter the characteristics of the barrier. The Schottky barrier height (SBH) forms a very important parameter of the diode as it controls the electrical transport across the barrier.…”
Section: Introductionmentioning
confidence: 96%
“…Any mechanism that modifies the properties of the interface such as the introduction of an interfacial layer [1][2][3][4], annealing [5,6], irradiation with gamma rays [7,8], protons [9][10][11][12][13][14] and neutrons [14][15][16], ion implantation, [17][18][19] and high-energy ion beam irradiation [20][21][22][23][24][25][26] are found to alter the characteristics of the barrier. The Schottky barrier height (SBH) forms a very important parameter of the diode as it controls the electrical transport across the barrier.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, the attenuation of sample C was much larger than that of sample B. In addition, Ar-implatation may cause ion damage-induced donors within the Si layer [14]. Therefore, the attenuation of sample C was much larger than that of sample A (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Similar result has also been reported in p-Si and n-Si Schottky diodes, in which high density of interface states were generated by Ar ion implantation. 18,19 It has been reported that the interface state density depended on the post annealing process for Si/Si and Si/GaAs junctions fabricated by SAB, which decreased as the annealing temperature increased. 17,20 The interface state density at the bonded Si/Si interface reduced to the smallest value after annealing at 1000 • C. Therefore, the annealing process with high temperature may be required for reducing the interface resistance of the bonded Al/Si junctions.…”
Section: Resultsmentioning
confidence: 99%